PROJECT MANAGEMENT SKILLS AND THEIR ROLE IN ORGANIZATIONAL EXCELLENCE: CASE STUDY IN THE GENERAL FERTILIZER INDUSTRY COMPANY / BASRA - Ass . Prof .Dr layla laftah Ali; Bareq Zaid Najm (Scholar Express Journals, 2025)
The study aimed to reveal the relationship between project management skills as an independent variable and its dimensions (leadership, communication, negotiation, problem solving, risk management) and its role in organizational excellence and its dimensions: subordinate excellence, organizational structure excellence, strategy excellence, leadership excellence
Keywords: Project Management Skills; Organizational Excellence